AntiHBc (total) as a Screening Assay for Safety of Donated Blood - Rahman, MZ; Alam, MR; Parveen, S; Ahmed, DS; Rahman, MA; Chowdhury, MS; Rana, MA; Masud, H (Bangladesh Medical Journal, 2014)
Detection of hepatitis B surface antigen (HBsAg) in blood is diagnostic for hepatitis B virus (HBV) infection. In blood bank, screening .for HBsAg is carried out routinely to detect HBV infection. Despite this, transfusion-associated HBV infection still occurs due to presence of occult HBV infection. The aim of this study was to detection of occult HBV infection among the HBsAg negative/ Anti-HBc(total) positive donar. A total of 52 patients negative for HBsAg, but positive for Anti HBc(total) were included in this study, All the patients were then investigated for determination of Anti-HBs titre and HBV-DNA (PCR).Out of 52 patients, HBV DNA was detected in 16 patients(8.32%). Overall, 18 patients (9.36%) out of 52 were found positive for AntiHBs antibody. Among antiHBs positive patients, who are supposedly protected against HBV infection, 6 (33.33%) patients had detectable HBVDNA.In conclusion, a considerable number of HBV infected donars remain undiagnosed, if only HBsAg is used for screening. Addition of AntiHBc(total) testing for donar screening will definitely eliminate HBV infected blood donations and help in reducing HBV transmission with its potential consequences. DOI: http://dx.doi.org/10.3329/bmj.v41i3.18958 Bangladesh Medical Journal 2012 Vol.41(3): 42-44